2011
DOI: 10.1007/s10035-011-0267-2
|View full text |Cite
|
Sign up to set email alerts
|

Interface roughness effect on slow cyclic annular shear of granular materials

Abstract: International audienceWe experimentally investigate the mechanical behaviour in cyclic shear of a granular material near a solid wall in a pressure controlled annular shear cell. The use of a model system (glass beads and saw-tooth shaped solid surface) enables the study of the influence of the wall roughness. After an initial shakedown procedure ensuring reproducible results in subsequent tests, wall shear stress S , volumetric variation Δ V , and the displacement field of the sample bottom surface, are recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Koval et al [78,79] shows a sharp increase of the apparent friction coefficient at the wall when increasing the roughness above 0.4 then a saturation. Moreover, the slip velocity increases when decreasing the roughness, in agreement with previous results [73].…”
Section: Rough Bottom Surfacesmentioning
confidence: 99%
“…Koval et al [78,79] shows a sharp increase of the apparent friction coefficient at the wall when increasing the roughness above 0.4 then a saturation. Moreover, the slip velocity increases when decreasing the roughness, in agreement with previous results [73].…”
Section: Rough Bottom Surfacesmentioning
confidence: 99%
“…The size polydispersity ensures that the flow profiles near the walls are not influenced by the ordering of grains [9,22]. While the bulk and boundary beads are always chosen of the same material, their size ratio δ=d wall /d bulk was varied in order to investigate the impact of the relative boundary roughness η which is defined by the normalized penetration of the flowing particles into the rough surface as η=1+δ− 1+2δ−δ 2 /3 [23,24]. For smooth walls η=0.…”
mentioning
confidence: 99%
“…The link of this macroscopic approach with the microscopic scale of the wall roughness compared to the particle size has been clarified experimentally by Koval et al (2011), in an annular configuration, by using wellcontrolled groove shapes on a shearing cylinder. It is shown that above some threshold of a properly defined dimensionless rugosity, the apparent wall friction coefficient undergoes a sharp transition and reaches approximately the internal coefficient of friction of the material, which justifies the present definition of rough walls.…”
Section: Boundary Condition At the Lateral Wallsmentioning
confidence: 99%